Overlapping Intimate Partner Violence and Sex Trading among High-Risk Women: Implications for Practice - Jiwatram-Negrón, Tina (Women Health, 2018)
Despite research indicating higher than average rates of intimate partner violence (IPV) across groups of vulnerable women, less is known about the prevalence and types of IPV experienced by women who trade sex for money, drugs, shelter or food, a high risk group for poor health and psychosocial outcomes. Using a cross-sectional design and multivariate logistic regression analyses, this study examined the relationship between IPV and sex trading in a convenience sample of 346 HIV-negative, drug-involved women in relationships, recruited during 2005–2010 in New York City. About 41% and 36% of participants reported lifetime and recent IPV, respectively, by their main partner, with significant differences by recent engagement in sex trading (p < 0.01). Results of multivariate analyses indicated that sex trading was associated with recent severe physical or sexual IPV (OR=3.07, p < 0.01) and that depression, having ever been married, child sexual abuse, and low income were associated with IPV (p < 0.05). Women who reported childhood sexual abuse and recent sex trading had a 7.37 higher odds (p < 0.01) for reporting severe physical or sexual IPV compared to those who reported neither. Findings highlight the need to expand screening and interventions among women who trade sex.